2013
DOI: 10.1099/ijs.0.034579-0
|View full text |Cite
|
Sign up to set email alerts
|

Oceanobacillus indicireducens sp. nov., a facultative alkaliphile that reduces an indigo dye

Abstract: An indigo-reducing facultatively alkaliphilic and halophilic strain, designated strain A21 T , was isolated from a fermented Polygonum indigo (Polygonum tinctorium Lour.) liquor sample aged for 4 days prepared in a laboratory. 16S rRNA gene sequence phylogeny suggested that strain A21 T was a member of the genus Oceanobacillus with the closest relative being the type strain of Oceanobacillus chironomi (similarity: 96.0 %). The cells of the isolate stained Gram-positive and were facultatively anaerobic straight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
30
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 37 publications
3
30
1
Order By: Relevance
“…Although similar to strains GD05 T and GD051 in that the predominant fatty acid was anteiso-C 15 : 0 , V. pantothenticus DSM 26 T had much larger proportions of anteiso-C 15 : 0 (49.7 %) and anteiso-C 17 : 0 (27.5 %). The fatty acid profile of Oceanobacillus iheyensis in this study was consistent with that described by Kim et al (2007), but was different from that reported by Hirota et al (2013) who detected anteiso-C 15 : 0 as the predominant fatty acid, which suggested that the fatty acid profile of Oceanobacillus iheyensis varies with culture conditions. In this study, the fatty acids of the new isolates and Oceanobacillus iheyensis were determined using cells cultured under the same conditions, so the comparison was credible.…”
Section: Sinibacillus Soli Gd051 (Kf188705)supporting
confidence: 73%
“…Although similar to strains GD05 T and GD051 in that the predominant fatty acid was anteiso-C 15 : 0 , V. pantothenticus DSM 26 T had much larger proportions of anteiso-C 15 : 0 (49.7 %) and anteiso-C 17 : 0 (27.5 %). The fatty acid profile of Oceanobacillus iheyensis in this study was consistent with that described by Kim et al (2007), but was different from that reported by Hirota et al (2013) who detected anteiso-C 15 : 0 as the predominant fatty acid, which suggested that the fatty acid profile of Oceanobacillus iheyensis varies with culture conditions. In this study, the fatty acids of the new isolates and Oceanobacillus iheyensis were determined using cells cultured under the same conditions, so the comparison was credible.…”
Section: Sinibacillus Soli Gd051 (Kf188705)supporting
confidence: 73%
“…Recently, a novel strain of Oceanobacillus indicireducens, which does not possess menaquinone, has been reported (Hirota et al, 2013).…”
mentioning
confidence: 99%
“…We have also isolated indigo-reducing bacteria belonging to the genus Amphibacillus, namely Amphibacillus indicireducens and Amphibacillus iburiensis (Hirota et al, 2013a, c). Furthermore, we have isolated Oceanobacillus indicireducens as an indigo-reducing bacterium (Hirota et al, 2013b). Surprisingly, although strains belonging to this genus possess isoprenoid quinone, this bacterium does not possess any isoprenoid quinone.…”
mentioning
confidence: 96%